Research on DNS implementation scheme of 5G enterprise private network - Shaolong YANG; Yingshuang LIU; Yingqi WEI; Yue HUANG (Dianxin kexue)
How to correctly parse the domain name of the internal and external networks in the 5G enterprise private network? It is a problem that needs to be solved urgently in the construction of the 5G private network.In the UPF sinking networking mode, 5G mobile users cannot use intranet DNS for domain name resolution.Four 5G enterprise private network DNS solutions were proposed and compared.